Integrating digital technologies in primary education: enhancing learning and engagement in young learners - Mukhina, Tetiana; Fedorchenko, Anastasiia (Kharkiv : H. S. Skovoroda Kharkiv National Pedagogical University, 2025)
This article explores the integration of digital technologies in modern primary education as a primary means of increasing student engagement and improving learning outcomes. The author examines various digital tools, including interactive whiteboards, tablets, and specialized educational software such as Khan Academy Kids and Minecraft Education Edition. The text highlights the importance of online learning platforms, virtual and augmented reality (VR/AR), and the introduction of coding and robotics to foster logical thinking and problem-solving skills. The study concludes that the systematic implementation of these resources allows for a personalized and interactive approach that aligns with the requirements of the New Ukrainian School and the demands of the modern information society.
Keywords: Digital technologies; primary education; student engagement; interactive learning; educational software; coding and robotics; distance learning; personalized learning; New Ukrainian School; digital competencies